THE RHEUMATOID HAND (Part II) - Yu A Olyunin; A V Smirnov; Yu A Olyunin; A V Smirnov (Современная ревматология)
The chronic inflammatory process characteristic of rheumatic arthritis (RA) leads over time to irreversible disorders caused by destruction of the articular cartilage and bones and lesions to the ligaments and tendons. In end-stage RA, the elasticity loss and sprain of the ligaments fixing the metacarpophalangeal articulations promotes finger subluxations and ulnar deviation. These may induce evident functional impairments and are generally associated with severe cartilage and bone destructive changes. Chronic inflammation of the radiocarpal articulation is usually attended by restriction of its movement. Soft tissue inflammatory edema in the carpal tunnel limited by rigid structures may result in the compression of the median nerve located here and in the development of the carpal tunnel syndrome. As the pathological process progresses, articular destructive changes considerably increase. There is bone erosion formation that may occasionally cause a complete destruction of the bone epiphyses. The typical sign of end-stage RA is wrist joint ankylosing, all the wrist bones being confluent into the common bone block.